Quantum metrology at the limit with extremal majorana constellations - Bouchard, Frederic; De La Hoz, P.; Bjork, G.; Boyd, R. W.; Grassl, Markus; Hradil, Zdenek; Karimi, Ebrahim; Klimov, A. B.; Leuchs, Gerd; Rehacek, Jaroslav; Sanchez-Soto, L. L. (Optica, 2017)
Quantum metrology allows for a tremendous boost in the accuracy of measurement of diverse physical parameters. The estimation of a rotation constitutes a remarkable example of this quantum-enhanced precision. The recently introduced Kings of Quantumness are especially germane for this task when the rotation axis is unknown, as they have a sensitivity independent of that axis and they achieve a Heisenberg-limit scaling. Here, we report the experimental realization of these states by generating up to 21-dimensional orbital angular momentum states of single photons, and confirm their high metrological abilities.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Metrology; Quantum information and processing; Quantum optics